Epigastric vein thrombosis with extension to the scrotal vein: case report - Rivero Rodríguez, Wilmer (2024)
We present the case of a male patient with no significant pathological history, who experienced abdominal pain radiating to the genital area. An incidental diagnosis of spontaneous venous thrombosis in the epigastric vein, extending to the scrotal vein, was made via Doppler ultrasound. The patient subsequently required anticoagulant therapy. Thromboembolic disease is a condition associated with cardiovascular complications, and its etiology is multifactorial. Doppler ultrasound was the diagnostic method of choice. This report describes a patientwith no relevant medical history, presenting with nonspecific abdominal pain and findings of thrombosis in the epigastric vein, extending to the scrotal vein. Complementary studies revealed elevated lupus anticoagulant levels, which supports the inclusion of this pathology in the differential diagnosis of abdominal pain.